METODE IMAM ASY-SYAUKANI DALAM MENYUSUN KITAB NAILUL AUTAR SYARH MUNTAQAL-AKHBAR - Fauzi Rizal (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
This article aims to describe the method of Imam Asy-Syaukani in compiling the book Nailul Autar Syarh Muntaqal-Akhbar. Kitab Nailul Authar is a book of shar from the book of legal hadith compiled by ibn Taimiyan